Evaluation of leprosy programme implementation according to WHO guidance in 8 provinces of the Central and the Upper-Southern region - สุจริยากุล อนุพงค์; เสริมฤทธิรงค์ ศิลธรรม; ธัญญกิตติกุล พจนา; อรุณภาคมงคล เพชรรัตน์ (Disease Control Journal, 2014)
This retrospective description study was conducted to evaluate the implementation of leprosy programme under the low endemic situation in accordance with the World Health Organization guidance. The leprosy programme has been implemented in 8 provinces namely Nakhon Pathom, Suphan Buri, Ratchaburi, Kanchanaburi, Samut Sakhon, Samut- Songkhram, Phetchaburi and Prachuap Khiri Khan in the responsible area of the Regional Office of Disease Prevention and Control 4 Ratchaburi. Related documents of the last 10 years (2003-2012) were gathered, then analysed and synthesised. Leprosy related data of the same period was gathered and analysed based on the indicators suggested by WHO and The International Federation of Anti-leprosy Association or ILEP It was found that leprosy programme in accordance with WHO guidance had implemented during the last 10 years (2003-2012). As a result, trend of leprosy incidence and potential source of transmission had gradually decreased. Recent transmission in community was rare. A case detection activity was not sufficient resulted in delayed in diagnosis of leprosy patients contributing to the high propor¬tion of disability grade 2 among newly detected cases. Prevention of disability activity was insufficient particularly prevention of further disability due to workloads and stigmatising attitudes of related health officers. Though the number of leprosy cases in 8 provinces was low, the number of people who had been discharged from treatment with leprosy-related disabilities still existed. The authors suggest continuing lep¬rosy programme in these provinces based on WHO guidance by adjusting activities to suit their contexts particularly prevention of further disability and rehabilitation services to those with leprosy-related disabili¬ties. This is to ensure the sustainability of leprosy services which new cases could access accurate treatment at health units nearby their homes, and those with disabilities are enabled to live normally in their own communities.